2019
DOI: 10.1021/acs.est.8b06954
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Ion-Size-Based Selectivity of Capacitive Deionization Electrodes

Abstract: Capacitive deionization (CDI) is an emerging water treatment technology often applied to brackish water desalination and water softening. Typical CDI cells consist of two microporous carbon electrodes sandwiching a dielectric separator, and desalt feedwater flowing through the cell by storing ions in electric double layers (EDLs) within charged micropores. CDI cells have demonstrated size-based ion selectivity wherein smaller hydrated ions are preferentially electrosorbed over larger hydrated ions. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Recently, Guyes et al presented a theory which predicted an enhancement of size-based selectivity towards K + over Li + and Na + , with increasing chemical charges in the micropore added by surface modification. 142 Dynamic calculations by Zhao et al using porous electrode theory for mono/di cation mixtures, with monovalent anions, showed that an electrode that initially selectively adsorbed monovalent cations, switched to the adsorption of divalent cations and desorption of the adsorbed monovalent cations later in the process, in line with experimental observations. Also, in Zhao et al, Gouy-Chapman-Stern (GCS) theory was used for mono/di cation mixtures containing the same monovalent anion, and combined with a model that describes ion transport to a planar charged wall.…”
Section: State-of-the-art Review Of Models In CDImentioning
confidence: 61%
See 1 more Smart Citation
“…Recently, Guyes et al presented a theory which predicted an enhancement of size-based selectivity towards K + over Li + and Na + , with increasing chemical charges in the micropore added by surface modification. 142 Dynamic calculations by Zhao et al using porous electrode theory for mono/di cation mixtures, with monovalent anions, showed that an electrode that initially selectively adsorbed monovalent cations, switched to the adsorption of divalent cations and desorption of the adsorbed monovalent cations later in the process, in line with experimental observations. Also, in Zhao et al, Gouy-Chapman-Stern (GCS) theory was used for mono/di cation mixtures containing the same monovalent anion, and combined with a model that describes ion transport to a planar charged wall.…”
Section: State-of-the-art Review Of Models In CDImentioning
confidence: 61%
“…In a mixture of ions of varying sizes, the excluded volume effect can result in a selectivity towards the smaller ion, captured by a difference in F exc,i between ions. We make use here of a very useful expression for the contribution to the chemical potential of a volume/excess term, m exc,i in the pore, which results in a contribution F exc,i = exp(Àm exc,i ) where we assume that this excess term is zero in bulk solution, which is approximately valid for a low salt concentration (order 10 mM) 142. For an ion inside a pore, m exc,i was derived to be155,156…”
mentioning
confidence: 99%
“…For instance, size-based selectivity of microporous carbon electrodes could be further enhanced by adding negatively charged carboxyl groups in the micropores through oxidation with nitric acid. The separation factor of K + over Li + increased from ∼1 to 1.84 thanks to functionalization ( Guyes et al., 2019 ). Vanadium was recovered using resin-activated carbon (RAC) composite electrodes.…”
Section: Electrochemical Separations For Selective Recoverymentioning
confidence: 99%
“…In total, the ion specific adsorption and the interaction between ions are time dependent with regard to the ion specific valence, diffusion coefficient, hydrated radius, the applied electricity, the pH, and the ion concentration [53,[82][83][84]. The ion volume exclusion interactions resulting in a preferred adsorption of ions with a smaller hydrated radius, were described by Suss and Guyes et al [85,86]. However, as currently shown in the study of Tsai et al [83], the influence of ion exchange membranes can reduce the affinity and thereby the selectivity.…”
Section: Specific Energy Consumptionmentioning
confidence: 99%